2020
DOI: 10.1038/s41598-020-60504-6
|View full text |Cite
|
Sign up to set email alerts
|

Western gorilla space use suggests territoriality

Abstract: The evolutionary origins of how modern humans share and use space are often modelled on the territorial-based violence of chimpanzees, with limited comparison to other apes. Gorillas are widely assumed to be non-territorial due to their large home ranges, extensive range overlap, and limited inter-group aggression. Using large-scale camera trapping, we monitored western gorillas in Republic of Congo across 60 km 2. Avoidance patterns between groups were consistent with an understanding of the "ownership" of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 56 publications
3
16
0
Order By: Relevance
“…However, this effect appears to be relatively weak. These findings support the hypothesis proposed in Morrison, Dunn, et al (2020) that gorillas show a form of territoriality where groups do not have hard territory borders, but rather,…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, this effect appears to be relatively weak. These findings support the hypothesis proposed in Morrison, Dunn, et al (2020) that gorillas show a form of territoriality where groups do not have hard territory borders, but rather,…”
Section: Discussionsupporting
confidence: 91%
“…If gorilla home ranges are aggressively defended, groups may avoid encountering their neighbours more when within their neighbours' home ranges. Indeed, there is evidence supporting this in western lowland gorillas (Morrison, Dunn, et al, 2020). The more effective territorial defence becomes at preventing neighbour intrusions, the harder it may become to detect from aggression.…”
Section: F I G U R Ementioning
confidence: 95%
See 1 more Smart Citation
“…The majority of studies have, however, only focused on one eastern sub-species ( Gorilla beringei beringei ), limiting an in-depth understanding of the behavioural diversity of gorillas. For instance, a recent study on western lowland gorillas ( Gorilla gorilla gorilla ) suggested that groups may show high levels of territoriality and actively defend core regions of their home ranges against neighbours 26 .…”
mentioning
confidence: 99%
“…Thus, a territory is defined as a specific type of home range characterized by aggressive protection or defense of its borders by the occupants against conspecifics (Burt, 1943). Territoriality is hereafter discussed as a behavioral trait which, in the absence of direction behavioral observations, may be predicted by measures of economic defendability and assess with tools such as the Defendability Index (Bartlett & Light, 2017; Brown, 1964; Mitani & Rodman, 1979; Morrison et al, 2020). The Defendability Index, one of the earliest developed models for assessing the potential for territoriality within populations and species, mathematically represents the relationship between daily path length and home range to reflect daily mobility and degree of defendability (Mitani & Rodman, 1979).…”
Section: Introductionmentioning
confidence: 99%